Taxonomic study of the genus Tenupalpa Lee et Li, 2021 (Lepidoptera: Gelechiidae: Thiotrichinae) from China, with descriptions of fifteen new species - Lee, Ga-Eun; Li, Houhun (Zootaxa, 2022)
Tenupalpa Lee et Li, 2021 (Gelechiidae: Thiotrichinae) was recently proposed based on a molecular and morphological study of the subfamily. It currently includes six species mainly known from Russia, Japan and India. In this paper, 15 new species from China are described: T. acutata sp. nov., T. acutimedia sp. nov., T. angulosa sp. nov., T. breviaedeaga sp. nov., T. zhengi sp. nov., T. crassimedia sp. nov., T. dissimilis sp. nov., T. falcata sp. nov., T. fuscalata sp. nov., T. immaculata sp. nov., T. isabellina sp. nov., T. magniguttata sp. nov., T. latifasciata sp. nov., T. perparviloba sp. nov. and T. uncativalva sp. nov. Also, T. xanthodora (Meyrick, 1923) comb. nov., and the original combination for Thiotricha glenias Meyrick, 1908 stat. rev. are proposed. Five species—Tenupalpa angustella (Omelko, 1984), T. biformis (Omelko, 1984), T. flavitermina (Kyaw, Yagi & Hirowatari, 2019), T. nephodesma (Meyrick, 1918) and T. venustalis (Omelko, 1984)—are reported from China for the first time, and two species—T. angustella and T. venustalis—are newly recorded from Korea. Photographs of adults, genitalia, and the eighth abdominal segment of males are illustrated, and a key to all known Tenupalpa species are provided based on external characters and male genitalia.